Implementation of Digital Parenting and the Development of Disciplinary Behavior in Early Childhood - Repni Ramadhani; Dian Miranda; Lukmanulhakim (CV. Yazri Aksara Nusantara, 2025)
The rapid advancement of digital technology has reshaped early childhood interaction and learning patterns, making digital parenting an essential component in ensuring safe and educational device use. This study aims to describe the implementation of digital parenting and its influence on the disciplinary development of children aged five to six at TK Negeri Pembina Pontianak Selatan. A descriptive qualitative approach was employed, involving five parents selected through purposive sampling. Data were collected through observation, semi structured interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that digital parenting practices include direct and application-assisted supervision, structured restrictions on duration and content, and communicative accompaniment through reflective dialogue and behavioral guidance. Children who received consistent support demonstrated stronger disciplinary tendencies, including improved time regulation, rule compliance, and smoother transitions between activities. The study concludes that digital parenting plays a significant role in shaping children’s discipline in the digital age. Its contribution lies in providing contextual empirical insights into how digital parenting is practiced in Indonesia and how it informs educational and familial strategies for supporting early childhood development.